#TITLE_ALTERNATIVE# - RIFAI (NIM 22404010); Pembimbing: Prof. Safwan Hadi, Ph.D., dan Dr. Eng. nining Sari Ningsih., AZIS
Mangrove vegetation in Mahakam Delta region have been degraded caused by human activity . Most of the mangrove forest have been deforested and converted to the agriculture farm, orchards, settlement and shrimp ponds.. Some research mentioned that mangrove degradation in Mahakam Delta is progressively increase. Nowadays deforested mangrove in Mahakam Delta is about 80% of the total surface of the delta plain. The degradation of mangrove vegetation in Mahakam Delta have lead to the land erosion and increase the amount of suspended sediment in the Mahakam Delta waters. Meanwhile the density of mangrove vegetation have also decreased. Thereby the mangrove vegetation lose its optimum ability as sediment trap. This matter progressively increased the total concentration of suspended sediment in the Mahakam Delta waters. The higher concentration of suspended sediment could hinder the sunlight penetration into water column and will decrease the water productivity. The research investigated mangrove density change and distribution of TSM concentration in Mahakam Delta using the descriptive method.. The datas that used are images of Landsat satellite (i.e. MSS 1983, TM 1992, TM 1998, ETM 2001) and the TSM field survey for year 2001. The images were analyzed with the statistical approach by applying the algorithms to retrieve the mangrove density class and the suspended sediment concentration. The result indicate that between year 1983 and year 2001, mangrove vegetation in Mahakam Delta have decreased by 36,30%. The very dense and dense mangrove vegetation classes have decreased by 51,49% while the sparse and very sparse mangrove vegetation classes have increased by 42,27%. In general, concentration of TSM in Mahakam Delta have increased by 52,96%. Statistically, the correlation between mangrove vegetation density change and the suspended sediment concentration have low correlation value. By visually it can be seen the relation between mangrove vegetation density changed and the suspended sediment concentration in Mahakam Delta.